Room temperature spontaneous exchange bias in BiFeO3 micro/nano powders synthesized by hydrothermal method. Issue 14 (1st October 2018) - Xu, Yu; Gao, Yafeng; Xing, Hongjie; Zhang, Jingji
Abstract: BiFeO2 micro/nano powders with tiny Bi2 Fe4 O9 or Bi25 FeO40 were synthesized through hydrothermal process. As a result, room temperature spontaneous exchange bias of 17–33 Oe was detected in all the samples, which was attributed to the exchange coupling between finer ferromagnetic particles and coarser antiferromagnetic particles. Upon applying field cooling with an external field of 4T, the exchange bias at 10 K increased markedly. Further, the samples did not show any bifurcation between the zero-field cooling and field cooling curves in the temperature range of 5–300 K.